Microstructure and Texture of a Spinel Corona Around a Basalt Hosted Corundum Xenocrystal. (6th January 2023) - Schuster, Roman; Tiede, Lisa; Ageeva, Olga; Griffiths, Thomas A; Abart, Rainer; Habler, Gerlinde
Abstract: The microstructural and textural characteristics of a spinel corona that formed around a faceted corundum xenocrystal by reaction with the hosting basaltic melt in the Siebengebirge volcanic field demonstrate that the crystallographic and shape preferred orientation of spinel is influenced by the orientation of the reaction interface with respect to the corundum crystal lattice. The spinel roughly shows the common topotactic orientation relationships with corundum, where one of the {111}_Spl planes is parallel to the (0001)_Crn plane, and three of the {110}_Spl planes are parallel to the {1010}_Crn planes. In detail, there are subtle but systematic deviations from this topotactic relationship due to small rotations about the c-axis and/or an a-axis of corundum. The former is observed when the corundum c-axis is closely parallel to the interface plane, while the latter require a corundum a-axis orientation perpendicular to the interface. In this case, the preferred sense of rotation depends on the sign of the a-axis direction, irrespective of the spinel growth direction being parallel or antiparallel to this axis. Additionally, the selection of either one or both of two spinel twin variants that equally fulfill the topotactic orientation relationship depends on the orientation of the corundum-spinel interface with respect to the lattices of both the corundum and the spinel. Finally, also the grain boundary character is controlled by the interface orientation and the corundum lattice. Despite the differences between corona segments, the nature of these textures are persistent along and across each segment. We emphasize that all these microstructural and textural features are ascribed to the period of spinel growth in magmatic environment. The extent to which prominent slip planes in spinel are aligned parallel with the corundum-spinel interface seems to be of crucial importance for the nature of the spinel texture and microstructure, indicating that the activity of dislocations pertaining to these slip systems ease the accommodation of lattice misfit across the corundum-spinel interface. By comparison with experimentally grown spinel layers, we infer predominantly interface reaction controlled growth of the studied spinel corona.